Research progress of autoimmune diseases based on induced pluripotent stem cells - Ren, Rutong; Jiang, Jinhe; Li, Xinxin; Zhang, Guirong (Frontiers in Immunology, 2024)
Autoimmune diseases can damage specific or multiple organs and tissues, influence the quality of life, and even cause disability and death. A ‘disease in a dish’ can be developed based on patients-derived induced pluripotent stem cells (iPSCs) and iPSCs-derived disease-relevant cell types to provide a platform for pathogenesis research, phenotypical assays, cell therapy, and drug discovery. With rapid progress in molecular biology research methods including genome-sequencing technology, epigenetic analysis, ‘-omics’ analysis and organoid technology, large amount of data represents an opportunity to help in gaining an in-depth understanding of pathological mechanisms and developing novel therapeutic strategies for these diseases. This paper aimed to review the iPSCs-based research on phenotype confirmation, mechanism exploration, drug discovery, and cell therapy for autoimmune diseases, especially multiple sclerosis, inflammatory bowel disease, and type 1 diabetes using iPSCs and iPSCs-derived cells.